Gender and predicting intentions among Malaysian teachers - Adam Assim, Mohd Ibrani Shahrimin; Janis, Salina; Yaccob, Yasmin; Mat Jusoh, Nurul Hidayu (Gyandhara International Academic Publications, 2020)
Purpose of the study: This study examined the predictors of intention in career development, specifically the intention of applying for promotion among Malaysian excellent teacher candidates. Methodology: The premise of the theoretical analyses in this study was based on the Theory of Planned Behavior. The correlational study design was employed to determine the relationship among the variables that ascertain any prediction towards the intention to apply for promotion. 500 respondents were sampled and consist of male (226) and female (274) teachers who are qualified to apply for promotion. Confirmatory Factor Analyses (CFA) was performed to test and validate the measurement model. Main Findings: This study had ascertained that gender does moderate relationships among the study's independent variables and the dependent variable. The result also indicates that the theory of planned behavior is applicable in predicting intention to apply for promotion. For teachers in Malaysia, the intention to apply for promotion will increase if the expectation of others towards applying for promotion also positively increase. Applications of this study: Gender-related specific assessment can be applied within the teachers’ performance appraisal system, particularly for the evaluation on ‘Guru Cemerlang’ or Excellent Teacher Award by the Ministry of Education in Malaysia. Novelty/Originality of this study: There is a scarcity of recent studies on the intention of Malaysian teachers to apply for promotion. By using the novel approach of Theory of Planned Behavior and the combination of structural equation modeling analyses, gender was found to moderate the relationship between the expectation of others and their intention to apply for promotion.